2019
DOI: 10.3390/f10121083
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity of the Soil Culturable Microbial Community in Eucalyptus Plantations of Different Ages in Guangxi, South China

Abstract: We selected five different ages of eucalyptus plantation sites to understand the culturable microbial functional diversity and the ecological functions of the soil from the eucalyptus plantations in Guangxi. We investigated the carbon source metabolic activity and diversity features of surface soil microbes using the Biolog EcoPlate method (Biolog Inc., Hayward, CA, USA), along with the microbial functional diversity and physicochemical properties of the soil. The results suggest that the carbon source utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(58 reference statements)
3
5
0
Order By: Relevance
“…AWCD is proportional to the number and species diversity of soil microbes that can metabolize carbon substrates, and it indicates the carbon source catabolic activity of microbial communities to utilize the carbon substrates [37,61]. In the present investigation, AWCD of soil microbial populations from cover crop and fertilizer source treatments exhibited classic microbial growth over time as the duration of incubation increased (Figure 1A,B), and these results were in accordance with other findings [40,53]. In this experiment, during the entire incubation period, native vegetation and cover crop mix (cereal rye + mustard) exhibited higher AWCD values than wheat, vetch, and cereal rye.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…AWCD is proportional to the number and species diversity of soil microbes that can metabolize carbon substrates, and it indicates the carbon source catabolic activity of microbial communities to utilize the carbon substrates [37,61]. In the present investigation, AWCD of soil microbial populations from cover crop and fertilizer source treatments exhibited classic microbial growth over time as the duration of incubation increased (Figure 1A,B), and these results were in accordance with other findings [40,53]. In this experiment, during the entire incubation period, native vegetation and cover crop mix (cereal rye + mustard) exhibited higher AWCD values than wheat, vetch, and cereal rye.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that mixed cover crops favor the release of certain allelochemicals, primary metabolites, and secondary metabolites significantly alter the soil microbial abundance and their functions [53]. However, cover crop biomass, quality, different soil types, C:N ratio of residues, environmental circumstances, and their interactions significantly influence the abundance and functional diversity of soil microbial populations [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, both the soil microbial activity and metabolic ability of the diseased plants were higher than the healthy plants. The pathogenic invasion of these plants altered the microbial community structure, which consequently increased their carbon source utilization, and this reduced the bioavailability of nutrients in plants, thereby aggravating the disease ( Lan et al, 2019 ). In this study, the soil microbial metabolism enhancement may be related to the increase in specific microbial groups that can utilize carbohydrates and carboxylic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptus, a rapidly growing tree species, has been extensively planted in southern China due to its economic value [3]; thus, it has become a dominant component of the timber plantations that have been established in the region over the past few decades [4,5]. Previous studies on Eucalyptus trees have primarily focused on their role as exotic species Forests 2024, 15, 423 2 of 14 in local ecosystems [6], exploring their impact on soil physicochemical properties [7], microbial community structure and function [8], and plant diversity [9]. These studies have provided insight into the effects of increasing Eucalyptus age on soil physicochemical properties, including stimulating enzyme activities such as phenol oxidase, peroxidase, and acid phosphatase [10].…”
Section: Introductionmentioning
confidence: 99%